2021
DOI: 10.1096/fj.202100332r
|View full text |Cite
|
Sign up to set email alerts
|

Adipose‐derived stem cells regulate metabolic homeostasis and delay aging by promoting mitophagy

Abstract: Tissues undergo a process of degeneration as the body ages. Mesenchymal stem cells (MSCs) have been found to have major potential in delaying the aging process in tissues and organs. However, the mechanism underlying the anti‐aging effects of MSC is not clear which limits clinical applications. In this study, we used adipose‐derived mesenchymal stem cells (ADSCs) to perform anti‐aging treatments on senescent cells and progeroid animal models. Following intervention with ADSCs, replicative senescence was delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 31 publications
0
21
1
Order By: Relevance
“…In addition, the characterization of the hASC included the assessment of the oxidative pro le in order to decipher bioenergetics ngerprint of the model, leading to similar trends between healthy controls and PD cases. So far, this is in contrast with suboptimal bioenergetics reported in other PD models (1), although comparable basal respiration has also been described in PD cybrid models compared to controls (29) and, similarly to this study, non-signi cant trends have also been described in hASC in the literature (17). Despite lack of signi cant differences in respirometry measurements, trends towards suboptimal maximal respiration capacity in PD hASC were con rmed in both oxygraphs compared with the healthy control hASC lines.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In addition, the characterization of the hASC included the assessment of the oxidative pro le in order to decipher bioenergetics ngerprint of the model, leading to similar trends between healthy controls and PD cases. So far, this is in contrast with suboptimal bioenergetics reported in other PD models (1), although comparable basal respiration has also been described in PD cybrid models compared to controls (29) and, similarly to this study, non-signi cant trends have also been described in hASC in the literature (17). Despite lack of signi cant differences in respirometry measurements, trends towards suboptimal maximal respiration capacity in PD hASC were con rmed in both oxygraphs compared with the healthy control hASC lines.…”
Section: Discussioncontrasting
confidence: 72%
“…The oxidative and lipolytic metabolic nature of neuronal and adipose tissues, respectively, confers a higher level of complexity in their relationship and in the molecular studies carried out in both biologic sources and derived cell models, especially, those related to bioenergetics. Although little is known about bioenergetic pro le of hASC, a recent study exploring hASC bioenergetics demonstrated for the rst time, that this stem cells can affect metabolic homeostasis by promoting damaged mitochondrial clearance through mitophagy, thereby delaying aging (17).…”
Section: Introductionmentioning
confidence: 99%
“…reported that SIRT1 is downregulated in hMSCs upon senescence caused by increasing passage number, and once overexpressed, it can reduce senescence in MSCs 23 . During replicative senescence in vitro, the population of senescent cells in various cell types including MSCs increases [26][27][28] . To confirm this in our MSCs, we checked the gene expression levels of P16, P21 and P53 at passages 1, 5 and 9 by quantitative PCR as their increases are known as markers of senescence 27 .…”
Section: Sirt1-nat Is Upregulated In Ad-mscs Upon Passage Related Sen...mentioning
confidence: 99%
“…During replicative senescence in vitro, the population of senescent cells in various cell types including MSCs increases [26][27][28] . To confirm this in our MSCs, we checked the gene expression levels of P16, P21 and P53 at passages 1, 5 and 9 by quantitative PCR as their increases are known as markers of senescence 27 . The relative expression of P16, P21, and P53 in Passage 5 and Passage 9 MSCs was significantly increased compared with passage 1 and passage 5 MSCs respectively (Fig.…”
Section: Sirt1-nat Is Upregulated In Ad-mscs Upon Passage Related Sen...mentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs), one of the prominent categories of adult stem cells (ASCs), are heterogenous, multipotent progenitor cells capable of delaying aging and restoring organ homeostasis following occurrence of inflammation, injury, and disease [ 1 , 2 , 3 ]. MSCs are primarily located in specialized niches across the multiple vascularized tissues and/or organs, such as bone marrow, adipose tissue, Wharton’s jelly, umbilical cord, dental pulp, and the placenta [ 4 , 5 , 6 , 7 ], although it is originally isolated from the bone marrow of the mammal [ 8 ].…”
Section: Introductionmentioning
confidence: 99%